The "worker model" and perception of environmental and occupational risks: The optimal use of a descriptive study - Facchini, LA; Weiderpass, E; Tomasi, E (Revista de saúde pública, 1991)
An attempt was made to identify the risks resulting from exposure to the chemicals to which workers are exposed as well as from the poor working conditions to which they are subject in a chemical and pharmaceutical factory. A descriptive study based on the "workers model" - a methodological approach developed in Italy in the 60's, was carried out. The activities of the different departments of the plant were reconstructed and the main chemicals used, the main physical complaints, the potential harms and the main environmental risks identified. The report on the harmful working conditions produced was used by the workers as a means of pressing the authorities into carrying out an inspection of the plant concerned to verify its accuracy. The report's findings have been confirmed and demonstrate the usefulness of the methological approach adopted. The workers' publicizing of the study's findings through the means of mass communication have helped to build up greater public awareness of the occupational and environmental risks of that particular industrial activity.